Rapid Cycle Deliberate Practice Pediatric Simulation Scenarios - Cara Doughty; Thomas Welch-Horan; Deborah Hsu; Elaine Fielder; Faria Pereira; Kim Little-Wienert; Brent Kaziny; Julie McManemy; Daniel Lemke (Association of American Medical Colleges, 2015)
Abstract Introduction Rapid cycle deliberate practice (RCDP) provides progressively more challenging simulation rounds in rapid repetition, with brief, usually directive expert feedback interspersed throughout the session. This is in contrast to traditional debriefing, which typically focuses on learning during debriefing after the scenario and most commonly seeks to uncover learners' frames through advocacy-inquiry debriefing but does not provide the opportunity for repetitive practice. Methods This curriculum is based on American Heart Association guidelines for pediatric resuscitation in two key algorithms, pulseless electrical activity and ventricular tachycardia. The curriculum provides two comprehensive RCDP pediatric resuscitation scenario sequences, as well as programs, operator instructions, and instructor guide. Using high-fidelity mannequins, learner teams of three to six residents participate in five or more progressively more difficult scenarios with directed instructor feedback and deliberate practice of resuscitation skills. The scenarios follow a sequence allowing the team to repetitively restart rounds of progressive difficulty, practicing the early stages of resuscitation and gradually incorporating more complicated components with each round. RCDP feedback is typically more directive and less reflective than traditional debriefing in order to allow the team to rapidly improve on key performance parameters based on established guidelines. When a round's objectives have been met, the instructor may choose to do a partial stop and restart if there is a brief correction that needs to be made, do a full stop if a team mistake requires additional discussion, or advance to the next round. Results We have taught these scenarios during a half-day dedicated to simulation for pediatric and emergency medicine residents during their pediatric emergency medicine rotation. At this time, we have taught 46 teams with three to six residents per team. Learners have expressed a high degree of satisfaction with the RCDP teaching methodology. Discussion The scenarios could also be used for other trainees or resuscitation teams with similar levels of expertise or could be modified for teams with more or less experience. We have also begun teaching with interprofessional teams of residents and nurses. Currently, we are conducting a randomized controlled trial comparing these RCDP scenarios with traditional scenarios.